Match without the audience - Competition without performance - Antonijevic, V.; Miloševic, M. (Serbian Journal of Sports Sciences, 2020)
The COVID-19 pandemic dramatically affects all aspects of organizing sporting events. The question raises whether sports competition can be possible without the audience, and what is the value of sports results if spectators do not attend and witness them? The aim of this paper is to analyze the observed problem within the theoretical framework of the performance studies, namely the theory of Erika Fischer-Lichte. Also, the aim of this paper is to introduce theoretical postulates of theatre and performance studies to sports researchers because they have great potential for application in the analysis of sport and its social role and characteristics. It was concluded that by abolishing the bodily co-presence of the audience and athletes autopoietic feedback loop is broken and the competition loses its performance properties, which is why sports results achieved without the presence of the audience cannot be valued in the same way as those achieved in front of the audience. The analysis lays the foundation for future empirical research as well as event organising and broadcasting practise improvement.